Energy Storage System Based on Ceremai Fruit Paste as Alternative Energy Source - Lalu Didik (Universitas Tidar, 2022)
This study aims to analyze the paste of ceremai fruit (Phyllanthus acidus) as a battery electrolyte replacing Manganese dioxide as an alternative energy source. The material used is battery that has carbon (C) and zinc (Zn) electrodes. Battery electrolyte derived from MnO2 was replaced with electrolyte from ceremai fruit paste. The variables measured were electric voltage, electric current and electric power. Based on the results of research and data analysis, the electrolytes from ceremai fruit paste can be used to replace the MnO2 electrolyte which is usually used as a battery electrolyte as an alternative energy source. Although the output voltage is lower. This can be overcome by assembling the bio-battery through a series circuit. The series of 11 bio-batteries circuit can light 6 volt lamp brightly because it can produce a voltage of 6.79 volts. The existence of a load on the lamp can be decreasing in source voltage. The decrease in source voltage followed by an increase in the value of the electric current.